Roles of glomerular endothelial hyaluronan in the development of proteinuria. Issue 17 (2nd September 2021) - Asai, Akimasa; Hatayama, Naoyuki; Kamiya, Keisuke; Yamauchi, Mai; Kinashi, Hiroshi; Yamaguchi, Makoto; Katsuno, Takayuki; Nobata, Hironobu; Watanabe, Kazushi; Wakatsuki, Akihiko; Aten, Jan; Maruyama, Shoichi; et al.
Abstract: Vascular endothelial cells are covered with glycocalyx comprising heparan sulfate, hyaluronan, chondroitin sulfate, and associated proteins. Glomerular endothelial glycocalyx is involved in protecting against induction of proteinuria and structural damage, but the specific components in glycocalyx that represent therapeutic targets remain unclear. Anti‐vascular endothelial growth factor (VEGF) therapy is associated with an increased risk of glomerular endothelial injury. This study investigated whether hyaluronan could provide a therapeutic target to protect against proteinuria. We conducted ex vivo and in vivo experiments to explore the effects of degrading glomerular hyaluronan by administering hyaluronidase and of supplementation with hyaluronan. We investigated hyaluronan expression using biotin‐labeled hyaluronan‐binding protein (HABP) in human kidney specimens or serum hyaluronan in endothelial injuries under inhibition of VEGF signaling. We directly demonstrated hyaluronan in glomerular endothelial layers using HABP staining. Ex vivo and in vivo experiments showed the development of proteinuria after digestion of hyaluronan in glomerular capillaries. Supplementation with hyaluronan after hyaluronidase treatment suppressed proteinuria. Mice in the in vivo study developed albuminuria after intraperitoneal injection of hyaluronidase with decreased glomerular hyaluronan and increased serum hyaluronan. In human kidneys with endothelial cell dysfunction and proteinuria due to inhibition of VEGF, glomerular expression of hyaluronan was reduced even in normal‐appearing glomeruli. Serum hyaluronan levels were elevated in patients with pre‐eclampsia with VEGF signaling inhibition. Our data suggest that hyaluronan itself plays crucial roles in preventing proteinuria and preserving the integrity of endothelial cells. Hyaluronan could provide a therapeutic target for preventing glomerular endothelial glycocalyx damage, including VEGF signaling inhibition. Abstract : Glomerular endothelial glycocalyx is involved in protection against induction of proteinuria and structural damage; however, which components in glycocalyx represent therapeutic targets remain unclear. Our data suggest that hyaluronan itself plays a crucial role in preventing proteinuria. Hyaluronan could provide a therapeutic target for preventing glomerular endothelial glycocalyx damage, including VEGF signaling inhibition induced by anti‐VEGF–VEGFR2 drugs and pre‐eclampsia.